Institutionalizing Pawongan: A Local Wisdom-Based Framework for Preventing Social Conflict in Multicultural Bali - Imanuel Adhitya Wulanata Chrismastianto; I Putu Sriartha (UIN Sunan Gunung Djati Bandung, 2025)
This study aims to examine the role of pawongan—a principle of interpersonal harmony in the Tri Hita Karana philosophy—as a local wisdom-based mechanism for preventing social conflict in Bali’s multicultural society. The urgency of this research lies in the rising identity-based tensions across Indonesia, which require conflict prevention strategies that do not solely rely on institutional or coercive approaches but instead draw from cultural values. This study employs a qualitative method with a library research design. The data consist of secondary sources such as peer-reviewed journal articles, academic books, policy documents, and relevant research reports. The data collection process followed a systematic procedure that included identifying key concepts, selecting primary literature on pawongan and Tri Hita Karana, and conducting thematic and narrative synthesis of the findings. The results reveal that pawongan has been actualized through four main strategies: first, the socialization of customary norms and rituals such as matatah and ngejot jerimpen; second, the promotion of interreligious tolerance by traditional and religious leaders; third, the integration of pawongan values into education and interfaith forums; and fourth, the revitalization of communal solidarity through customary institutional structures. These strategies demonstrate that pawongan is not merely a normative teaching, but a functional framework for community-based peace governance. The findings reaffirm the relevance of local wisdom in shaping inclusive conflict prevention policies and sustainable peacebuilding. The originality of this research lies in its reinterpretation of pawongan as an institutionalized and context-specific value model that contributes a new perspective to the discourse on conflict resolution in Southeast Asia.